2015
DOI: 10.1007/s12199-015-0499-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors and human health: fibrous and particulate substance-induced immunological disorders and construction of a health-promoting living environment

Abstract: Among the various scientific fields covered in the area of hygiene such as environmental medicine, epidemiology, public health and preventive medicine, we are investigating the immunological effects of fibrous and particulate substances in the environment and work surroundings, such as asbestos fibers and silica particles. In addition to these studies, we have attempted to construct health-promoting living conditions. Thus, in this review we will summarize our investigations regarding the (1) immunological eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…The evidence of dysregulation of the immune system caused by silica was confirmed epidemiologically by frequent complications of autoimmune diseases, as well as cell biological investigations which revealed chronic activation of responder and regulatory T cells (Treg; CD4 + , CD25 + and forkhead box P3 (FoxP3) positive inhibitory cells) caused by silica particles (1214). Considering the malignant complications in asbestos-exposed patients, it is possible that asbestos exposure promotes the reduction of tumor immunity in these patients (15,16). It is on the basis of this viewpoint that we examined the effects of asbestos on human immune cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence of dysregulation of the immune system caused by silica was confirmed epidemiologically by frequent complications of autoimmune diseases, as well as cell biological investigations which revealed chronic activation of responder and regulatory T cells (Treg; CD4 + , CD25 + and forkhead box P3 (FoxP3) positive inhibitory cells) caused by silica particles (1214). Considering the malignant complications in asbestos-exposed patients, it is possible that asbestos exposure promotes the reduction of tumor immunity in these patients (15,16). It is on the basis of this viewpoint that we examined the effects of asbestos on human immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…The original MT-2 cells (Org) showed apoptosis with activation of pro-apoptotic MAPK, mitochondrial apoptotic pathway and ROS production, when exposed transiently to ChA, ChB or CRD with relatively high doses of these fibers (2124). However, when Org cells (MT-2 cells that never encountered asbestos fibers) were exposed continuously with relatively low doses of fibers (doses that do not yield apoptosis in less than half of the cells) for more than one year, these sublines (designated as CB1 to 3, CA1 to 3, and CR1 exposed to ChB, ChA and CRD, respectively, and established independently) exhibited changes in cell features (15,22,24). The cells showed acquisition of asbestos-induced apoptosis, alteration of cytokine production, excess production of interleukin (IL)-10 and transforming growth factor (TGF)-β, reduced production of interferon (IFN)-γ, resistance to TGF-β-induced growth inhibition, and enhanced phosphorylation and expression of β-actin on their cell surface (15,2225).…”
Section: Introductionmentioning
confidence: 99%
“…During these long latency periods, and under conditions leading to the occurrence of other malignancies such as cancers of the larynx, gastrointestinal tract and bladder (22,23), it is thought that individuals exposed to asbestos and possessing asbestos fibers in their body might have reduced antitumor immunity due to asbestos exposure and recurrent and chronic encounters between intra-body fibers and immune competent cells. It is on this basis that we have been investigating the immunological effects of asbestos on immune competent cells, particularly in regard to antitumor immunity (19)(20)(21)40).…”
Section: Discussionmentioning
confidence: 99%
“…The overall findings concerning the immunological effects of asbestos on human immune competent cells indicated that chronic exposure to asbestos causes a reduction in antitumor immunity (19)(20)(21). This suggests that asbestos-exposed individuals possess gradually reduced antitumor immunity and subsequent increased susceptibility to the onset of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although the physiological effects caused by silica and asbestos differ, including those produced by fibers and particles, asbestos fibers may influence the various circulating immune cells in a manner similar to silica particles. In particular, the immunological effects of asbestos may be the reduction of antitumor immunity as evidenced by malignant complications of asbestos exposure detected after a long latent period such as 30 to 40 years for MM [25][26][27].…”
Section: Introductionmentioning
confidence: 99%